Analisis Ilmu Dakwah Serta Keterkaitannya Dengan Cabang Ilmu Lainnya - Fazzila, Fazzila; Hendra, Tomi; Nisa, Rabiatun; Meldi, Nayla Shafwa (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2024)
Da’wah and da’wah sciences two complementary concepts. As a family of sciences, da’wah sciences does not stand alone, but has a relationship with other auxiliary sciences. The purpose of this writing is to analyze the science of da'wah and its relationship with other branches of science. The type of research used uses a qualitative literature review approach. The results obtained are that da'wah is an activity of calling or conveying, as well as an invitation to carry out the commands of Allah SWT. and abandoning its prohibitions based on the teachings of the Islamic religion which aims for good in this world and the afterlife. The science of da'wah is a space that becomes a system for implementing da'wah. The science of da'wah itself is divided into two, namely; Islamic da'wah and general da'wah. Da'wah science has two objects, in the form of material objects and also formal objects. These two objects are interrelated and complement the systematics in the science of da'wah. The conclusions drawn by the science of da'wah also do not stand alone. Science is interconnected and interconnected. Likewise with the science of da'wah. Da'wah science is related to communication science, sociology and psychology.